2002
DOI: 10.3928/0191-3913-20020301-07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Levodopa and Carbidopa in Human Amblyopia

Abstract: Background: To assess the role of continuous therapy for 3 weeks with levodopa and carbidopa in the management of human ambiyopia in children and adults. Method: There were 88 amblyopic eyes of 82 subjects included in this double masked randomized prospective clinical trial. Levodopa and carbidopa combination in 2 different dosage schedules were given to both adults and children. The response was monitored of the improvement in visual acuity, contrast sensitivity, and visually evoked potentials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…However, the use of a neurotransmitter (levodopa) to increase the plasticity of the amblyopic brain is still controversial. 52,53 In a recent study, we demonstrated that perceptual learning may be a useful approach to improving visual performance in adult amblyopia. 46 We asked seven adult observers with amblyopia to practice a repetitive position-discrimination task.…”
mentioning
confidence: 99%
“…However, the use of a neurotransmitter (levodopa) to increase the plasticity of the amblyopic brain is still controversial. 52,53 In a recent study, we demonstrated that perceptual learning may be a useful approach to improving visual performance in adult amblyopia. 46 We asked seven adult observers with amblyopia to practice a repetitive position-discrimination task.…”
mentioning
confidence: 99%
“…Occlusion has been supplemented by near activities 32 and by the administration of neurotransmitters or their analogs, such as levodopa. [33][34][35][36] More mainstream treatment alternatives include optical penalization with over-plus lenses over the dominant eye, 37 occlusion of the spectacle lens using adhesive tape, Bangerter foils, 38 or Min lenses 39 for amblyopic patients who wear glasses, and perhaps most successfully and widespread, atropine penalization of the preferred eye.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…This, according to the sparse literature [11], predicted a very unfavorable prognosis. Use of levodopa to ameliorate the amblyopia (see, for example, [7,10]) was considered inadvisable due to the patient's antidepressant medication.…”
Section: Case Reportmentioning
confidence: 99%